FISH PRODUCTION AND FISH POPULATION CHANGES IN SOME SOUTH INDIAN RESERVOIRS - Sreenivasan, A (Indian Journal of Fisheries, 2011)
When the rivers are impounded, qualitative and quantitative changes intheir biota are bound to occur. Effect of such changes in the fish populationsand also the physico-chemical environment and fish yield are to be known indetail in order to plan suitable management programmes on reservoir fisheries.It is also necessary to know the potential productivity of the reservoirs in orderto determine the optimum level of exploitation. Stocking programmes have to bebased on repopulation trends of the exploited fish.